Riding in the shadows: The reaction of the British print media to Chris Froome's victory in the 2013 Tour de France. (June 2016) - Groves, Mark; Griggs, Gerald
On 21 July 2013 Chris Froome became only the second British cyclist to win the Tour de France. This paper examines how the events surrounding Froome's victory in the 2013 Tour de France were reported in the British (London-based) print media the day after his victory. Data were collected from nine different daily newspapers on 22 July with a total of 52 pages of coverage devoted to the story. Thematic coding revealed that, despite a comprehensive victory, Froome appeared to be framed as being in the shadow of two other prominent cyclists. Firstly, Froome's victory appeared to be framed within a moral panic surrounding the use of performance-enhancing drugs in cycling, with his achievements partially overshadowed by the 'folk devil' that is Lance Armstrong. Secondly, the data suggested that narratives around British national identity were prevalent within the reporting of Chris Froome, with this reporting particularly focused on the issue of his African heritage. Initial analysis indicated that the British print media actually celebrated Froome's African roots, suggesting that they may be starting to embrace a new post-imperial form of national identity that reflects the multicultural or hybrid nature of 21st century Britain. However, we would also argue that Froome may only have achieved an ambivalent position as a British hero and that his African heritage – although celebrated to an extent – means that in the eyes of the British print media he still sits below Sir Bradley Wiggins in what might be described as a 'hierarchy of Britishness'.